"DEVELOPMENT STRATEGY" BASED ON EDUCATION AND HUMANITY AS A SOURCE OF SUSTAINABLE DEVELOPMENT OF SOCIETY (Scientific journal of the Fergana State University, 2025)
This article presents proposals and recommendations for the preservation of national values and spiritual heritage, the implementation of the concept of "New Uzbekistan - an enlightened society", and shows that the contradictions in society also exist in the inner nature of man, and analyzes the inability of moral values to reconcile these contradictions.